Getting published in the humanities what to know, where to aim, how to succeed - Kahan, Jeffrey, 1964- (McFarland & Co., 2012)
"In most humanities fields, securing tenure proves impossible without at least one book under your belt. Yet despite the obvious importance of academic publishing, the process remains an enigma to most young scholars. By outlining a step-by-step approach to publishing, this indispensable manual removes much of the mystery surrounding an essential component of an academic career"--Provided by publisher.